1992
DOI: 10.1161/01.str.23.12.1767
|View full text |Cite
|
Sign up to set email alerts
|

Arginine vasopressin V1-antagonist and atrial natriuretic peptide reduce hemorrhagic brain edema in rats.

Abstract: Background and Purpose: Injection of arginine vasopressin into the cerebral ventricles in animals with brain injury increased brain water, whereas injection of atrial natriuretic peptide reduced water content. Therefore, to determine the role of endogenous arginine vasopressin in brain edema, we attempted to inhibit edema from a hemorrhagic lesion with an arginine vasopressin V t receptor antagonist or atrial natriuretic peptide.Methods: Adult Sprague-Dawley rats with hemorrhages induced by 0.4 IU bacterial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 42 publications
3
22
0
Order By: Relevance
“…Our results are well in agreement with other experimental studies showing that AVP is involved in the pathophysiology of acute brain damage, for example, after subarachnoid or intracerebral hemorrhage (Doczi et al, 1984;Rosenberg et al, 1992), cortical focal lesions (Reeder et al, 1986;Bemana and Nagao, 1999), traumatic brain injury (Armstead, 2001), global cerebral ischemia (Liu et al, 1991(Liu et al, , 1996Ikeda et al, 1997), and permanent focal cerebral ischemia (Dickinson and Betz, 1992;Shuaib et al, 2002). The amount of AVP mRNA and of AVP protein increase after experimental cerebral ischemia (Liu, 1992;Liu et al, 2000) and levels of AVP are elevated in the CSF of stroke patients (Barreca et al, 2001).…”
Section: Avp During Pathologic Conditions Of the Brainsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are well in agreement with other experimental studies showing that AVP is involved in the pathophysiology of acute brain damage, for example, after subarachnoid or intracerebral hemorrhage (Doczi et al, 1984;Rosenberg et al, 1992), cortical focal lesions (Reeder et al, 1986;Bemana and Nagao, 1999), traumatic brain injury (Armstead, 2001), global cerebral ischemia (Liu et al, 1991(Liu et al, , 1996Ikeda et al, 1997), and permanent focal cerebral ischemia (Dickinson and Betz, 1992;Shuaib et al, 2002). The amount of AVP mRNA and of AVP protein increase after experimental cerebral ischemia (Liu, 1992;Liu et al, 2000) and levels of AVP are elevated in the CSF of stroke patients (Barreca et al, 2001).…”
Section: Avp During Pathologic Conditions Of the Brainsupporting
confidence: 93%
“…Our results show that centrally applied AVP receptor antagonists do not have an effect on blood pressure, CBF, and body temperature as also observed by others (Rosenberg et al, 1992). Hence, hypothermia or any other disturbances of animal physiology can be ruled out as a possible nonspecific mechanism of the neuroprotection observed in the current study.…”
Section: Modelsupporting
confidence: 88%
See 1 more Smart Citation
“…21,[24][25][26] Previous work demonstrating that vasopressin may induce brain edema 20,21,56 is supported by multiple studies showing that edema is abolished by blocking the V1aR receptors. [24][25][26][27][28][29] The present results demonstrate that V1aR inhibition accelerates the recovery of [Na + ] e supporting its potential to blunt the ionic dysfunction that leads to edematous changes. Taken together, out findings suggest that SR49059 and other V1aR inhibitors may have potential as therapeutic agents for treating cellular edema by both speeding post-injury ionic recovery and reducing injury-induced elevation of ICP following CCI.…”
Section: Beneficial Effects Of V1ar Inhibition By Sr49059supporting
confidence: 65%
“…Further, experimental models of intracerebral hemorrhage, middle cerebral artery occlusion, ischemia, and cold and traumatic brain injury have demonstrated that V1aR inhibition reduces brain edema. [22][23][24][25][26][27][28][29][30][31] The underlying mechanism of this response has been attributed to either modulation of vasopressin in the brain parenchyma 17 or its interaction with aquaporin-4 (AQP4). AQP4 is the predominant water channel in the brain and has a significant role in the pathophysiology of brain edema.…”
Section: Introductionmentioning
confidence: 99%